Arqueobotánica del sitio Soria 2 (Catamarca, Argentina) - Petrucci, Natalia Silvana (2019)
Background and aims: In the valley of Santa María or Yocavil the archeobotanical studies included the systematic recovery of remains by means of the flotation technique. However, plant archaeological remains have been scarcely studied so far. The aim of this paper is to present the identification of plant remains recovered by flotation and contribute to the interpretation, in this case, the site early Soria 2 located in the Valley, from analysis of this research. M&M: The flotation technique implemented was mechanical. Quantification methods used were: absolute amount, relative frequency, density and ubiquity. Once identified, the taxa were analyzed according to modes of association with human communities: wild, weedy and domesticated. Results: The following taxa could be taxonomically identified: Trichocereus sp., Geoffroea decorticans, Chenopodium sp., Opuntia sp., Prosopis spp., Zea mays and Solanaceae. When grouping the taxa according to their degree of association we see that the ruderal weeds are the ones with the highest densities, followed by the wild ones, while the rest presented similar density percentages. Conclusions: The differences of presence / absence of taxa and proportions between the different spaces that make up the domestic unit, could indicate differential activities carried out in the past, suggesting practices with different spatial anchorage. The carpological set of the site suggests the presence and the use of disturbed and undisturbed environments next to cultivation spaces indicated by domesticated plants and agricultural weeds for early moments.